PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP PADA SMK BHARA TRIKORA - Herly Nurrahmi (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2020)
One of the information that is needed by a school is information about the payment of tuition fees. Information on the payment of tuition fees makes it easier for the Administration to check data on student monthly tuition payments which were previously recorded manually, now it is computerized. So that officers will not have difficulty in finding student data. This study uses the Waterfall method. The result of the research is an application of the education guidance tuition fees payment system of SMK Bhara Trikora uses the VB.NET program to create a system interface, Ms. Access as a Database Management System and Crystal Report to display tuition fees payment transaction reports. Keywords: Payment System, and VB.NET